Efektivitas Intervensi Motor Imagery (MI) terhadap Rehabilitasi Pasien Post stroke: A Systematic Review - Bernadetta Germia Aridamayanti; Gevi Melliya Sari; Wimar Anugrah Romadhon (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Background: Motor Imagery (MI) is an intervention to improve motor skills in post stroke hemiparesis patients by focusing on weak body parts. Objective: To describe the effectiveness of providing MI in the rehabilitation of post stroke patients. Method: The database used to identify suitable articles obtained from Scopus, ProQuest and Pubmed was limited to the last 5 years of publication from 2016 to 2020, English, and fulltext articles. The literature review used the keyword "Motor Imagery" AND "Stroke Rehabilitation". In searching articles used "AND". Only 8 articles met the inclusion criteria. This review was from these 8 articles. Results: MI has effectiveness in cognitive, sensory and motor post-stroke patients by stimulating neuroplasticity in various areas of the brain so that it accelerates the increase in O2, glucose and various metabolites that lead to increased regional metabolism through dilation of cerebral arterioles and capillaries. MI which is given routinely will help the recovery of motor function of post-stroke patients and increase patient independence. Conclusion: MI has a lot of effectiveness in the rehabilitation of post stroke patients. Suggestion: MI is considered necessary to be applied in hospitals in Indonesia. Keywords: motor imagery; stroke; rehabilitation ABSTRAK Latar belakang: Motor Imagery (MI) merupakan intervensi untuk meningkatkan keterampilan motorik pada pasien hemiparesis post stroke dengan berfokus pada bagian tubuh yang lemah. Tujuan: Untuk menjabarkan efektivitas pemberian MI pada rehabilitasi pasien post stroke. Metode: Database yang digunakan dalam penelitian ini adalah Scopus, Proquest dan Pubmed terbatas untuk publikasi 5 tahun terakhir dari 2016 hingga 2020, full text article dan berbahasa Inggris. Kata kunci yang digunakan adalah “Motor Imagery” AND “Stroke Rehabilitation”. Systematic review ini menggunakan 8 artikel yang sesuai dengan kriteria inklusi. Hasil: MI memiliki efektivitas pada kognitif, sensorik dan motorik pasien post stroke dengan merangsang neuroplastisitas pada berbagai area otak sehingga memperlancar peningkatan O2, glukosa dan berbagai metabolit yang mengarah ke peningkatan metabolisme regional melalui dilatasi arteriol serebral dan kapiler. Motor Imagery (MI) yang diberikan secara rutin akan membantu pemulihan fungsi motorik pasien post stroke dan meningkatkan kemandirian pasien. Simpulan: MI memiliki banyak efektivitas pada rehabilitasi pasien post stroke Saran: MI dipandang perlu untuk diterapkan di rumah sakit yang ada di Indonesia. Kata kunci: motor imagery; stroke; rehabilitation